Accounting for Individual Differences in Decision-Making Competence: Personality and Gender Differences - Weller, Joshua; Ceschi, Andrea; Hirsch, Lauren; Sartori, Riccardo; Costantini, Arianna (Frontiers in Psychology, 2018)
Emerging research has highlighted the utility of measuring individual differences in decision-making competence (DMC), showing that consistently following normatively rational principles is associated with positive psychosocial and health behaviors. From another level of analysis, functional theories of personality suggest that broad trait dimensions represent variation in underlying self-regulatory systems, providing a mechanistic account for robust associations between traits and similar life outcomes. Yet, the degree to which broad dispositional personality dimensions predict global tendencies to respond rationally is less understood. In a large online community sample (N=804), we tested the associations between HEXACO personality dimensions, a 6-factor structural trait model, and a subset of DMC indicators (Applying Decision Rules, Resistance to Framing, Recognizing Social Norms, and Consistency in Risk Perception). Additionally, we examined gender differences across the DMC, first considering the potential for measurement noninvariance across groups for the DMC. We observed partial measurement invariance between men and women; only the Applying Decision Rules scale showed evidence of differential functioning across groups. Controlling for these differences, analyses revealed that higher Conscientiousness, Honesty/Humility, and Openness were associated with higher DMC scores. In contrast, Emotionality and Extraversion demonstrated gender-specific associations. Specifically, low Extraversion was associated with higher DMC scores for men, whereas higher Emotionality was associated with higher DMC scores for women. Our results suggest that traits related to self-regulatory functions of cognitive and behavioral control, and cognitive flexibility are associated with an increased tendency to engage in rational thought.